2008
DOI: 10.1007/s00439-008-0610-9
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of ROBO1/DUTT1 and ROBO2 loci in early dysplastic lesions of head and neck: clinical and prognostic implications

Abstract: Deletion of chromosomal 3p12.3 was suggested to be associated with dysplastic lesions of head and neck. This region harbors two candidate tumor suppressors ROBO1/DUTT1, ROBO2 and two non-coding RNAs (ncRNAs) located at intron 2 of ROBO1/DUTT1. Aim of this study is to understand the role of these genes in development of head and neck squamous cell carcinoma. A collection of 72 dysplastic lesions and 116 HNSCC samples and two oral cancer cell lines were analyzed for ROBO1/DUTT1 and ROBO2 deletion and promoter me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 25 publications
4
23
1
Order By: Relevance
“…Similar findings have also been reported in carcinomas of the cervix, lung, and breast 13,15,28,29 In our previous study of ROBO1 alteration (deletion/ methylation) in HNSCC development, frequent alteration of ROBO1 was seen in dysplastic and invasive lesions. 7 In this study, to understand the association of SLIT2-ROBO1 in the development of HNSCC some common samples of dysplastic lesions (n ¼ 25) and invasive lesions (n ¼ 72) of the previous study were used along with some freshly collected samples (dysplastic lesions: 5; invasive lesions: 56). The ROBO1 alteration had concordance with the previous study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar findings have also been reported in carcinomas of the cervix, lung, and breast 13,15,28,29 In our previous study of ROBO1 alteration (deletion/ methylation) in HNSCC development, frequent alteration of ROBO1 was seen in dysplastic and invasive lesions. 7 In this study, to understand the association of SLIT2-ROBO1 in the development of HNSCC some common samples of dysplastic lesions (n ¼ 25) and invasive lesions (n ¼ 72) of the previous study were used along with some freshly collected samples (dysplastic lesions: 5; invasive lesions: 56). The ROBO1 alteration had concordance with the previous study.…”
Section: Discussionmentioning
confidence: 99%
“…7 Mice harboring deletions of exon 2 of ROBO1 spontaneously developed bronchial epithelial hyperplasia, indicating it as a candidate tumor suppressor gene (TSG). 8 Our previous study also found a high frequency of molecular alterations (deletion/ methylation) and concordant reduced expression of ROBO1 in head and neck lesions, indicating importance of this gene in the development of HNSCC.…”
Section: Statement Of Clinical Relevancementioning
confidence: 99%
See 1 more Smart Citation
“…Many of these protective genes encode membrane bound or secreted proteins, and their expression is downregulated in GI carcinomas (20,54,60,61). Muc1, 5ac, and 6 are highly enriched and are main constituents of the mucus barrier in the stomach, which protects the underlying epithelium from proteases, mechanical trauma, and pathogenic microorganisms (35).…”
Section: Epithelial Protection Regeneration and Innate Immune Responsementioning
confidence: 99%
“…As an example, molecular alterations of ROBO1 and -2 genes, mapping into 3p12 band, are known to be linked to carcinogenesis (Ghosh et al 2009), whereas zinc finger protein 133 and protein tyrosine phosphatase , receptor type, T genes, located in 20p11.23 and 20q12-q13 regions, respectively, are recognized regulators of cell growth, differentiation, mitotic cycle, and oncogenic transformation (Lee et al 2007;Scott and Wang 2011).…”
Section: Discussionmentioning
confidence: 99%